Analisis Kinerja Persimpangan Tanpa Rambu Lalu Lintas: Dampak terhadap Keamanan dan Potensi Kecelakaan di Persimpangan Sungai Pauh Jl. Prof. A. Madjid Ibrahim - Basrin, Defry; Mutia, Eka; Pramudia, Orys (Portal: Jurnal Teknik Sipil, 2025)
Abstract — Traffic signs play an important role in regulating smoothness, orderliness and safety on the road. The absence of traffic signs will have an impact on increasing the risk of accidents. This is because drivers do not have a clear indication of safe speed, road priority, or potential dangers ahead. Pauh River Junction Jl. Prof. A Majid Ibrahim is an intersection that is categorized as busy with activity. However, this intersection does not have traffic signs, which are visual communications that function to provide important information to drivers regarding road conditions, speed limits, directions to take, and potential dangers. The research was conducted to analyze intersection performance using the 1997 Indonesian Road Capacity Manual (MKJI) method and the Traffic Conflict Technique (TCT) method used to predict the level of accident ratios, as well as extracting further information regarding driver behavior in dealing with conflicts. Based on the research carried out, a DS of 0.5 was obtained, which indicates that the intersection performance has medium service status. Meanwhile, the potential for accidents shows a figure of 5.5% with an average speed of serious conflict between 18-25 km/hour. The distance that has the potential to cause accidents tends to be around 2.6 m - 3.0 m. Obtained 48% for the category of drivers who were involved in conflicts due to accelerating the vehicle's speed.